Why network approach can promote a new way of thinking in biology - Giuliani, Alessandro; Filippi, Simonetta; Bertolaso, Marta (Frontiers in Genetics, 2014)
This work deals with the particular nature of network-based approach in biology. We will comment about the shift from the consideration of the molecular layer as the definitive place where causative process start to the elucidation of the among elements (at any level of biological organization they are located) interaction network as the main goal of scientific explanation. This shift comes from the intrinsic nature of networks where the properties of a specific node are determined by its position in the entire network (top down explanation) while the global network characteristics emerge from the nodes wiring pattern (bottom up explanation). This promotes a ‘middle-out’ paradigm formally identical to the time honored chemical thought holding big promises in the study of biological regulation.